BOOK REVIEW: TIMING GRACE. REFLECTIONS ON THE TEMPORALITY OF PREACHING - M. Laubscher (Acta Theologica)
Cilliers, J. (Stellenbosch: African Sun Media, 2019), 96pp. Price: R440. ISBN: 978-1-928480-22-8 is reviewed by M. Laubscher.